A Fluorescent Detection for Paraquat Based on β-CDs-Enhanced Fluorescent Gold Nanoclusters - Hong-Xin Ren; Min-Xin Mao; Min Li; Cun-Zheng Zhang; Chi-Fang Peng; Jiang-Guo Xu; Xin-Lin Wei (Foods, 2021)
In this report, a fluorescent sensing method for paraquat based on gold nanoclusters (AuNCs) is proposed. It was found that paraquat could quench both glutathione-capped AuNCs (GSH-AuNCs) and β-cyclodextrin-modified GSH-AuNCs (GSH/β-CDs-AuNCs). The modification of β-CDs on the surface of GSH-AuNCs obviously enhanced the fluorescence intensity of GSH-AuNCs and improved the sensitivity of paraquat sensing more than 4-fold. This sensibilization was ascribed to the obvious fluorescence intensity enhancement of GSH-AuNCs by β-CDs and the “host–guest” interaction between paraquat and β-CDs. The fluorescence quenching was mainly due to the photoinduced energy transfer (PET) between GSH/β-CDs-AuNCs and paraquat. With the optimized β-CDs modification of the GSH-AuNC surfaces and under buffer conditions, the fluorescent detection for paraquat demonstrated a linear response in the range of 5.0–350 ng/mL with a detection limit of 1.2 ng/mL. The fluorescent method also showed high selectivity toward common pesticides. The interference from metal ions could be easily masked by ethylene diamine tetraacetic acid (EDTA). This method was applied to the measurement of paraquat-spiked water samples and good recoveries (93.6–103.8%) were obtained. The above results indicate that host molecule modification of fluorescent metal NC surfaces has high potential in the development of robust fluorescent sensors.